DEVELOPING SUPPLEMENTARY READING COMPREHENSION MATERIALS FOR AUTOMOTIVE MECHANICAL SKILLS PROGRAM - Widyati, Widyati; Regina, Regina; Sutapa, Y. Gatot (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This present study was administered to develop supplementary reading comprehension materials for the tenth grade students of Automotive Mechanical skills Program. The writer applied Research and Development study (R&D). The participants of the research were tenth grade students of Automotive Mechanical Skills Program of SMK Negeri 2 Pontianak in academic year 2015/2016 and also the English teacher who taught the class. The data of the present study were collected by interview, questionnaire, observation table checklist and validation table checklist. This study found that the problem in the existing reading material was irrelevancy of the materials with the program of the students. Furthermore, about 74,1% students stated that they need reading materials related to their program. Therefore reading comprehension materials needed to be developed. From the finding, there were eight requirements needed to be met. They were suited to syllabus, related to the automotive mechanical skills program, contained vocabularies related to program, contained interesting materials, contained enjoyable activities, could be coped by the teacher and students, related to the students’ prior knowledge and must be contextual. As the result, the reading materials developed by the writer had met all the requirements. It got positive responses from both the teacher and students. Keywords: Developing Material, Reading Comprehension, Automotive Mechanical Skills Program.